Effect of Silane-Containing Universal Adhesives on the Bonding Strength of Lithium Disilicate - Kim, Yu-Ri (Materials (Basel), 2021)
The purpose of this study was to investigate the effect of silane-containing universal adhesives on the bonding strength of lithium disilicate. Two-hundred-and-forty lithium disilicate blocks were divided into 16 groups according to the following surface treatments: hydrofluoric acid (HF)-treated or not, silane-treated or not, and the type of universal adhesive used (All-Bond Universal (ABU); Prime & bond (PB); Clearfil Universal Bond (CU); Single bond Universal (SBU)). After surface treatment, resin discs were bonded to each lithium disilicate using dual-cure resin cement. Bonded specimens were stored in distilled water for 24 h and then subjected to microtensile bond strength (μTBS) test. Failure modes were examined under stereomicroscope. Microscopic observation of bonded interfaces was analyzed using scanning electron microscopy. The μTBS data were statistically analyzed. Regardless of silane treatment, all groups treated with HF showed higher bonding strengths compared to those that were not treated with HF (p < 0.05). In groups treated with HF, the bonding strength increased after silane application (p < 0.05) except PB and CU (p > 0.05). Adhesive failures were dominant in all groups, but some mixed failures were observed in ABU treated with HF and silane. While most of the specimens that were not treated with silane after HF application only showed loose bonding between the ceramic and resin cement due to partial gaps, the specimens treated with silane application after HF showed a tight ceramic–resin interface. In conclusion, the silane in universal adhesives did not effectively improve the bonding strength between lithium disilicate and resin cement.